2015
DOI: 10.1155/2015/725082
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Physical Quality Criteria of Bulakbaşı Stream in Turkey and Usage of Drinking, Fisheries, and Irrigation

Abstract: Water quality parameters were analyzed in Bulakbaşı stream. The in situ measurements and laboratory analyses were made on water samples taken from 4 sampling points on the Bulakbaşı stream monthly. During the study, the average water temperature as 16.3°C, dissolved oxygen (DO) 12.91 mg/L, oxygen saturation (OS) 152.8%, pH 8.25, electrical conductivity (EC) 779.6 μS/cm, salinity 0.435‰, chloride 83.97 mg/L, calcium 56.5 mg/L, magnesium 57.1 mg/L, total hardness 391.1 mg/L CaCO3, carbonate 0 mg/L, bicarbonate 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…2). Concentration of NO 3 -N in this study showed similar value with other studies [4,33,34]. Water on all stations in this study is included non degree of restriction on use because the NO 3 -N is less than FAO limit 5 mg.L -1 [32].…”
Section: Results and Discussion Water Physico-chemical Qualitysupporting
confidence: 89%
See 1 more Smart Citation
“…2). Concentration of NO 3 -N in this study showed similar value with other studies [4,33,34]. Water on all stations in this study is included non degree of restriction on use because the NO 3 -N is less than FAO limit 5 mg.L -1 [32].…”
Section: Results and Discussion Water Physico-chemical Qualitysupporting
confidence: 89%
“…However, now days most of the rivers were severelly polluted due to anthropogenic activities [1] and pollution of surface water became crucial environment issue all over the world [2]. Low water quality caused by pollution decrease water availability for directly or indirectly use, including for irrigation [3] or recreational water [4]. Natural process such as decaying, erosion, and flooding as well as anthropogenic activities like urbanization, industry and agriculture are the factors that causing pollution on the surface water [5].…”
mentioning
confidence: 99%
“…The pH with a mean value of 6.46±0.07 as shown in Fig. 2 was observed to fall slightly within the 6.5-8.5 ranges set for first-class drinking water [28,29]. The highest value of 6.53 was observed in FCE (6.53) and the least in 80 units (6.39).…”
Section: Physicochemical Parameter Analysismentioning
confidence: 75%
“…respectively. The level of phosphorus in quality drinking water is recommended at maximum 400ug/l and according to the ranges observed in this study, the water samples for the study locations are in first grade [28,29,31].…”
Section: Showing the Tds Ec And Hardness Values In Water Samples Frmentioning
confidence: 83%
See 1 more Smart Citation